Data_Sheet_1_Can policies improve language vitality? The Sámi languages in Sweden and Norway.pdf - Anika Lloyd-Smith; Fabian Bergmann; Laura Hund; Tanja Kupisch (2023)
Introduction Language policies are often aimed at changing language behaviours, yet it is notoriously difficult to assess their effects. This study investigates language use and competence in the Indigenous Sámi populations of Norway and Sweden in light of the national-level policies the two countries have adopted. Methods We provide a cross-country comparison of relevant educational, linguistic and budgetary policies in Sweden and Norway. Next, we present novel data from a survey with 5,416 Sámi and non-Sámi participants in 20 northern municipalities, examining Sámi language use and proficiencies across generations and contexts. Lexical proficiency in North Sámi was tested in a small subset of participants. Results Sámi language use has dropped considerably over the past three generations. Only a small proportion of Sámi are highly fluent and use a Sámi language with their children (around 4% in Sweden and 11% in Norway). One fifth of Sámi adults use a Sámi language at least ‘occasionally’, and use is most common in the home context. Sámi language knowledge remains negligible in the majority population. Discussion The higher levels of language use and proficiency in Norway seem at least in part to reflect the more favourable policies adopted there. In both countries, more work is needed to increase speaker numbers, also in the majority population.